Rituximab therapy in pediatric pemphigus patients: A retrospective analysis of five Turkish patients and review of the literature - ÖZGEN, ZÜLEYHA (WILEY, 2019)
Background/Objectives There is inadequate knowledge regarding rituximab (RTX) administration in autoimmune bullous diseases (AIBDs), disease prevalence, clinical characteristics, and treatment outcomes within pediatric populations due to the rarity of AIBDs affecting the pediatric age group. The aim of this retrospective analysis was to evaluate the effectiveness, safety of RTX, and treatment outcomes in Turkish pediatric patients with pemphigus vulgaris (PV) and to review the literature. Methods Five patients under 18 years of age and diagnosed with PV received RTX treatment and were identified in four dermatology departments of Turkey. Results The mean age of the patients at the time of RTX therapy initiation was 15 years (range: 11-17 years), and the total duration of follow-up after RTX therapy was 42.6 months (range: 19-60 months). All patients showed a clinical response. At the last visit, complete remission off therapy was achieved in three patients. The remaining two patients achieved partial remission off therapy. No adverse events were observed. Conclusions This retrospective case series of five pediatric patients showed that RTX treatment can be effective and safe for the treatment of recalcitrant PV in pediatric patients. With increasing evidence, RTX is a good treatment choice in adults and pediatric patients with pemphigus.
Keywords: childhood pemphigus; juvenile pemphigus; pediatric pemphigus; rituximab; therapy; JUVENILE PEMPHIGUS; ADJUVANT THERAPY; VULGARIS; CHILDHOOD; DISEASE; EPIDEMIOLOGY; PREDNISONE; TURKEY